2019
DOI: 10.1111/phpp.12477
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation to prevent and disrupt Staphylococcus aureus biofilm under different media conditions

Abstract: Objective The goal of this work was to investigate the photodynamic activity of 5,10,15,20‐tetrakis[4‐(3‐N,N‐dimethylaminopropoxy)phenyl]chlorin (TAPC) and zinc(II) 2,9,16,23‐tetrakis[4‐(N‐methylpyridyloxy)]phthalocyanine iodide (ZnPPc4+) as photosensitizers to inactivate Staphylococcus aureus biofilms and prevent their formations in different culture media. Methods We incubated S aureus biofilms in different culture media: tryptic soy (TS), nutrient (N), Müeller Hinton (MH) broth, TS with glucose 2 and 5% (w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…2.12 Scanning electron microscopy of S. aureus biolm on PEDOT-C 60 S. aureus biolm on PEDOT-C 60 samples were prepared as previously reported. 47,48 The samples were then covered with gold and examined with a scanning electron microscope. SEM images were obtained with a eld emission scanning electron microscope FE-SEM, Sigma Zeiss (LAMARX facilities).…”
Section: Pdi Experiments: Assembled Biolmsmentioning
confidence: 99%
“…2.12 Scanning electron microscopy of S. aureus biolm on PEDOT-C 60 S. aureus biolm on PEDOT-C 60 samples were prepared as previously reported. 47,48 The samples were then covered with gold and examined with a scanning electron microscope. SEM images were obtained with a eld emission scanning electron microscope FE-SEM, Sigma Zeiss (LAMARX facilities).…”
Section: Pdi Experiments: Assembled Biolmsmentioning
confidence: 99%
“…This suggests that in the most difficult cases, APDT may be a valid treatment option. There are promising studies in the literature demonstrating in vitro anti-biofilm staphylococcal action of APDT with various photosensitisers and blue light, [ 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ] but which are lacking in vivo histological evaluation of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that a single aPDT treatment significantly decreased bacterial viability by >99.9% for all three bacterial strains. It is well established that biofilm-associated bacteria are typically less sensitive to aPDT than planktonic cells ( 17 , 18 ). Thus, it was not unexpected that PS concentration and irradiation times had to be increased to achieve similar photoinactivation rates within the biofilms.…”
Section: Discussionmentioning
confidence: 99%